Dyslipidemia Factors on Male Workers at Power Plant in Jepara - Wisnu Harmawan; Indri Hapsari Susilowati (Humanistic Network for Science and Technology (HNST), 2022)
According to WHO data 2021 that 41 million people died every year in the world caused by non-communicable diseases or equivalent to 71% of death globally and more than 15 million people who died from non-communicable diseases were aged between 30-69 years. The biggest contributor to death from non-communicable diseases in the world is cardiovascular disease which is up to 17.9 million people every year. Atherosclerosis is the basis of heart disease and blood vessels where dyslipidemia is one of its main risk factors. Based on Riskesdas data in 2018, it was found that the prevalence of dyslipidemia case in Indonesia is quite worrying where 28.8% of population aged 15 years old and more had total cholesterol level above 200 mg/dL; 24.3% has HDL level less than 40 mg/dL; 73.8% had LDL level above 100 mg/dL and 27.09% had triglyceride level above 150 mg/dL. The objective of this study was to identify and analyze factors such as age, body mass index/BMI and work status which have a relationship with the incidence of dyslipidemia so that the incidence of dyslipidemia can be prevented. This study was conducted in the one of power plant operation and maintenance company in Jepara Regency where 84.55% of male workers experienced dyslipidemia incidents based on medical check-up results in 2021. The design used in this study was an observational analytic with cross-sectional design. The population in this study was 220 male workers of that company which this study used a total population sampling technique. Data processing was carried out with Chi-Square and Z-test statistical tests. Data obtained that 186 of 220 male workers of that company with dyslipidemia incidence. The results of the study showed that there was a significant relationship between the incidences of dyslipidemia in male workers with their age (p=0.002) and body mass index/BMI which 129 male workers have obesity (p=0.001) and there was no relationship between dyslipidemia incidence by male workers with work status (p=0.505). According to this study, the company needs to initiate health/fitness programs for workers and improve health promotion programs, especially about health lifestyle topics.